Practitioner counseling associated with improved opioid disposal among families of postoperative pediatric patients. Issue 5 (October 2021) - Butler, Christi; Kornberg, Zachary; Copp, Hillary L.
Summary: Background: Death from opioid-related overdose has doubled in recent years. Interestingly, there has been a similar increase in the number of opioid prescriptions. Medical providers, unfortunately, have contributed towards this rise in prescriptions. To combat the opioid epidemic, numerous efforts have been made to focus on the medical field and its role in the opioid epidemic. Proposed solutions for reduction of circulating opioids have included such measures as education, monitoring programs, alternative pain management strategies, and improved opioid disposal. Objectives: We aimed to assess if counseling is associated with proper opioid disposal among families of post-operative pediatric patients. Study design: We conducted a cross-sectional, convenience sample study of families of post-surgical, pediatric patients at a single academic institution. Participants completed a survey during their postoperative visit assessing opioid requirements, storage and disposal during and after the postoperative period, and if they were counseled by any medical professional on proper disposal methods. We used multivariable logistic regression to evaluate the association between the independent variables and the primary outcome. Results: We enrolled 180 participants, mean age of 8 years. Thirty-four percent reported having no opioid medication remaining at follow up because the medication was either consumed or the prescription was not filled. Sixty-six percent had leftover medication at the time of follow up. Sixty-six percent of participants knew the proper opioid disposal methods. However, only 22% of patients with leftover medication properly disposed of the medication. Patients who were counseled about proper opioid disposal were 3 times more likely to practice proper disposal practices than those who were not (p < 0.01). Discussion: Our study uniquely look at opioid consumption, disposal rates, and the effect of counseling in a diverse post-surgical pediatric population. Our findings confirm similar observations in the literature with regards to low opioid consumption, but in a larger, more surgically diverse cohort with a 100% response rate. Limitations included a lack of demographic diversity and lack of data measuring the impact of timing or frequency of counseling on opioid disposal practices. Further research goals would be to evaluate the effectiveness of counseling on proper opioid disposal, and the influence of timing and various counseling methods. Conclusions: Most patients do not use all of their opioid medication prescription. Proper opioid disposal counseling by a medical professional may play an important role in adherence to recommended opioid disposal practices. Summary Figure Orange bar represents the method that participants thought was the correct way to dispose of opioids versus the blue bar which represents what participants actually did to dispose of their opioid medication. Note: participant numbers total to greater than 180 as participants could select more than one option. Summary Figure